Glycation Induced 3D Structural Changes of Human Serum Albumin in Diabetes Mellitus (Medical Forum Monthly, 2020)
Objective: The present study was planned to find out the structural changes of proteins due to glycation in diabetic and non-diabetic patients.Study Design: Experimental Study.Place and Duration of Study: This study was conducted at the Civil Hospital Faisalabad and Bioinformatics Lab GC University Faisalabad from January 2018 to June 2019.Materials and Methods: A total 60 subjects, 30 without diabetes and 30 with diabetes were selected. From each subject 0.5 ml was drawn from antecubital vein using plastic disposable syringe. Serum was separated after centrifugation of clotted blood. Serum glucose, total proteins and albumin was immediately analyzed and a part of serum was stored in storage cup for future analysis of glycated albumin. In silico prediction models was used to predict change in glycated proteins, for this purpose different bioinformatics tools were used in present research work. These tools helped to construct three dimensional (3D) models of proteins before glycation and after glycation as well as their stability after glycation.Results: The study revealed that structural and functional features of glycated HSA, isolated from diabetic patients were significantly different from the HSA isolated from non-diabetic subjects. These findings suggest that active sites of HSA may not be available under extensive glycation, leading to the impairment of its important functions. Results amino acid residue at 114 position was glycated, the normal functioning of human serum albumin was stopped. Ramachandran plot was constructed for glycated and non-glycated human serum albumin, hence showed UN functionality of protein with red color. Thus, glycated HSA may be involved in the pathogenesis of diabetes and its complications.Conclusion: The overall glycation rate, the thermodynamics of this process, and the modification rate in certain regions were considered in such studies. The role of glycation conditions in the types of modifications formed was also examined.